From Status-Based to Offense-Based Jurisdiction: Reformulating Military Court Competence over Assault and Other Ordinary Crimes against Civilians in Indonesia - Fadil Albani (Acta Law Journal, 2026)
This article examines the jurisdiction of Indonesian military courts over ordinary crimes committed by soldiers against civilians. The legal problem is not the absence of a formal rule, because Article 74 of Law Number 34 of 2004 keeps Law Number 31 of 1997 applicable until a new Military Courts Law is enacted. The problem lies in the prolonged transitional regime that has preserved a status-based jurisdictional model despite the reform-oriented direction of Article 65 paragraph (2) of the Armed Forces Law. Using normative juridical research with statutory and conceptual approaches, this article analyzes whether ordinary crimes such as assault or collective violence against civilians should remain within military court competence. The article argues that jurisdiction should not be determined solely by the perpetrator's military status, but by the nature of the offense, the legal interest harmed, the victim's status, and the connection between the offense and military duty. The main contribution of this article is an offense-based and interest-based model of jurisdiction. Under this model, military courts remain competent over pure military offenses and service-related crimes, while ordinary crimes committed by soldiers against civilians should be adjudicated by general courts. Such reform is necessary to strengthen legal certainty, equality before the law, due process, civilian supremacy, and public accountability.